Some epidemiological features of BCoVs infection in Al-Qadisiyah Province by using real time-qPCR technique - Khetam Qaid Mayee (Al-Qadisiyah Journal of Veterinary Medicine Sciences, 2014)
This study was carried out to evaluate some epidemiological features of Bovine Coronavirus infection by using one-step real-time fluorogenic quantitative reverse transcription polymerase chain reaction (RT-qPCR) assay based on SYBR Green I dye in detection. Coronaviruses detected by the same nucleocapsid (N) gene primers under 98% similarity with HECV-4408 (human enteric Coronavirus) in children according to NCBI with product size 124bp. 285 fecal samples have been examined by routine methods against pathogenic bacteria in the intestines (E.coli, Salmonella Spp.) and Cryptosporidium parvum, the samples positive for the parasite submitted to molecular testing because they may be mixed with coronavirus infections. 100 samples were screened for the presence of BCoVs antigens by using an immunochromatographic rapid test as a field fast test. Where 44% of samples showed positivity to BCoVs, out of 50 samples submitted to quantitative reverse transcription (RT-qPCR) assay. Out of 50 – 31 samples had been positive. We found that distribution of BCoVs was significantly higher in rural areas 33.3%-87.5% as compare to cities 71.4%-75%, the infection in males reach to75% vas 53.5% in females, high infection rate 62.9% in < 1- 4 months age as compared with > 1 month age 62.9%. The results of infection rate showed high percentage during February 77.7% while the percentage on (January, December, March, and April) was (66.6%, 66.1%, 54.5%, and 50%) respectively.